Institutions, Inequality and Development - Ziegler, Maria (Goettinger Studien zur Entwicklungsoekonomik / Goettingen Studies in Development Economics, 2012)
The book focuses on the linkages between institutions, inequality and development. It analyzes formal political institutions, in particular the relationship between democracy and human development. It also centers on informal social institutions leading to the exclusion of population groups such as women and indigenous people. To measure these institutions in the case of gender inequality the Social Institutions and Gender Index (SIGI) and its five subindices are proposed and for the indigenous «disadvantage» the indigenous dummy is used. The dissertation shows that formal and informal institutions affect human development, the governance of a society and inequality.